2011
DOI: 10.1007/s00415-011-6140-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptoms screening in the early stages of Parkinson’s disease

Abstract: Psychiatric complaints are common in Parkinson's disease (PD), and have a significant influence in disease outcome and quality of life. Little attention has been paid to psychiatric symptoms at early stage disease. We aimed to screen a population of early stage PD patients for psychiatric symptoms and to study the relation with motor and cognitive function. Thirty-six early stage PD patients underwent motor [Hoehn and Yahr (HY), Unified Parkinson's Disease Rating Scale] and cognitive [Frontal Assessment Batter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…Psychosis prevalence was similar for NMSS and PPQ scales, and higher than in most studies. This was also detected in a previous investigation in early stage Portuguese PD patients, and could be related to the older mean age of our PD population7 or to the tendency to tolerate low intensity psychotic symptoms rather than using neuroleptics, which is suggested by the reduced number of patients who were under antipsychotics compared to those who scored positive in the psychosis scales.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Psychosis prevalence was similar for NMSS and PPQ scales, and higher than in most studies. This was also detected in a previous investigation in early stage Portuguese PD patients, and could be related to the older mean age of our PD population7 or to the tendency to tolerate low intensity psychotic symptoms rather than using neuroleptics, which is suggested by the reduced number of patients who were under antipsychotics compared to those who scored positive in the psychosis scales.…”
Section: Discussionsupporting
confidence: 73%
“…Cognitive dysfunction, for instance, was found to be increased in populations with lower education levels4, the total prevalence of NMS was found to be increased in regions with less health care availability5 and the prevalence of hallucinations lower in countries with less access to dopaminergic treatment4. The relation between symptoms has also been assessed, suggesting a relation between cognitive deficits and non-tremor motor symptoms6; depression and cognitive dysfunction7; psychosis and sleep dysfunction89; apathy and depression or executive dysfunction10. However, many studies have focused only on a particular set of symptoms.…”
mentioning
confidence: 99%
“…Both Maia et al [29] and Harbishettar et al [30] did not find significant OCS in their PD patients. However, Alegret et al [31] found OCS to be especially prevalent in particular PD groups, while Bugalho et al [5] and Siri et al [32] found a higher percentage of OCS in PD, using the same psychopathological screening scale. Studies addressing the relation between OCS and ICDs in PD are even scarcer.…”
Section: A Connection Between Icds Andmentioning
confidence: 96%
“…Psychiatric disorders, such as psychosis, depression and anxiety, are frequently found in PD [5]. The spectrum of behavioural disorders in PD has recently been widened to include a group of conditions known as impulse control disorders (ICDs).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study carried out in patients with Parkinson's disease in early stages, the prevalence of anxiety was about 27% (Bugalho et al, 2012).…”
Section: Introductionmentioning
confidence: 98%